Community Development Department Web Portal for Southern Border of Thailand - Ayuya, Tirayut (2005)
The advancement of tools for database information development has broadened its usage in management and administrative factor of goods and services lately. Most organizations managed their information via the latest database technology. The benefit derived from the usage of database makes the OTOP (One Tambon One Product) organization to develop and use this database. With the usage of Web-Portal for OTOP system, the management can do transaction, search, edit and add information like province, procedure, product-type, addresses, order, payment and so forth to enhance competitive demand within the nation. This methodology used is Object-Oriented with Unified Modeling Language Approach that was being applied for analyzing and designing system. The system implementation uses UML notation supported to design Database, User Interface, and Procedure of the System such as Class Diagram. Use Case Diagram, and sequence Diagram. The OTOP organization can centralize its information in Web Portal and also online database. This online database can assist the customers either to order or to purchase the OTOP products online. The customers can surf information and easily access to the system anytime anywhere. The outcome and evaluation of the project are discussed at the end of the dissertation then discussion on the project significance, recommended work for future study and research in the development of concepts, tools, techniques and methodologies.